Modeling the Composites for Magnetoelectric Microwave Devices - Mirza Bichurin; Oleg Sokolov; Sergey Ivanov; Elena Ivasheva; Viktor Leontiev; Vyacheslav Lobekin; Gennady Semenov (Sensors, 2023)
Many studies of the ME effect have been carried out in the microwave range in connection with the possibility of creating new electronic devices. One of the main microwave ME effects is the FMR line shift in an electric field, and the purpose of this article is to compare the FMR line shift in the ME structure in an electric field for a number of ferromagnetic metals, their alloys, and YIG ferrite using various piezoelectrics. This article discusses the regimes when the bias field is directed along the main axes of the magnetic component, while, as is known, the observed effect is due only to deformation. As a result of the study, ME structures with maximum and minimum microwave ME effects were found. In addition, the “substrate effect” in the piezoelectric YIG-GGG structure is considered.